2003
DOI: 10.1381/096089203764467216
|View full text |Cite
|
Sign up to set email alerts
|

Gastroscopic Removal of an Adjustable Gastric Band after Partial Intragastric Migration

Abstract: The endoscopic technique is beneficial even when the intraluminal migration is partial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 10 publications
2
35
0
1
Order By: Relevance
“…We have defined three stages of migration depending on the degree of migration into the gastric lumen. Endoscopic removal is feasible provided that band has partially or totally migrated [16,21]. Nevertheless it requires specific equipments and skilled endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…We have defined three stages of migration depending on the degree of migration into the gastric lumen. Endoscopic removal is feasible provided that band has partially or totally migrated [16,21]. Nevertheless it requires specific equipments and skilled endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopic approach with a device designed to cut the band (the Gastric Band Cutter, AMI) has been proposed, especially when the band has almost completely migrated into the stomach. 10 In our study, we review our experience with endoscopic removal of eroded gastric bands using this special endoscopic instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Egberts et al [2], based on a literature review, reported that the rate of re-erosion with this strategy was low, with weight loss maintained at the same rate as that of other bariatric procedures. During the same period, the endoscopic band removal technique was developed [13,[36][37][38]. The endoscopic technique implies that 50 % or more of the band, together with its lock, had migrated into the gastric lumen.…”
Section: Discussionmentioning
confidence: 99%